(untitled) (Wallingford, UK, 2003)
This book highlight work on the pests and diseases that may cause spoilage, adverse health effects and loss of the crop after harvest and discusses new techniques for the safe, effective and environmentally friendly management of stored commodities. The content cover the future of stored product protection and the impacts of global issues, food safety, chemiscal and physical control, and processing and applications
Keywords: Food storage pests,Food; Control,Storage